Guidelines for the control and monitoring of methane gas on continuous mining operations - Chilton, J. E.; Goodman, Gerrit V. R.; Taylor, Charles D. 1946- (Information circular (National Institute for Occupational Safety and Health) ;, 2010)
This publication demonstrates how existing and new engineering controls can be used to reduce face methane levels on continuous mining operations.